2023
DOI: 10.1002/ehf2.14373
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnostic value of high‐sensitivity cardiac troponin T for cancer treatment‐related cardiac dysfunction: a meta‐analysis

Xinfang Lv,
ChenLiang Pan,
Huan Guo
et al.

Abstract: Early diagnosis of cancer treatment-related cardiac dysfunction (CTRCD) is important as cancer therapy increases the risk of cardiac dysfunction. High-sensitivity cardiac troponin T (hs-cTnT) is a highly specific marker of myocardial injury. However, its diagnostic value for CTRCD has not been systematically evaluated. This meta-analysis aimed to evaluate whether hs-cTnT could be used as an early diagnostic biomarker for CTRCD. We systematically surveyed PubMed, Embase, Cochrane Library, and Web of Science dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…Japanese researchers showed that early relative worsening of >15% in GLS was significantly associated with hsTnI elevation [57]. As shown recently, hs-cTnT testing can improve the accuracy of CTRCD clinical diagnosis [58].…”
Section: Discussionmentioning
confidence: 88%
“…Japanese researchers showed that early relative worsening of >15% in GLS was significantly associated with hsTnI elevation [57]. As shown recently, hs-cTnT testing can improve the accuracy of CTRCD clinical diagnosis [58].…”
Section: Discussionmentioning
confidence: 88%
“…Herein, we discussed the role of ferroptosis in anticancer-drug-induced myocardial injury. However, in actual clinical practice, the prediction of CTRCD via elevated blood troponin T levels is limited in sensitivity [ 51 ], suggesting that ferroptosis might not be severe enough to cause heart failure. Our study suggests that impairment of myocardial energy metabolism caused by anticancer drugs may contribute to cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In patients on immune checkpoint inhibitors, elevated conventional Tn was associated with myocarditis and the risk of MACE, including cardiovascular death, cardiogenic shock, cardiac arrest, or complete heart block [ 237 ]. Because Tn elevations can be detected prior to echocardiographic changes, the assay can allow clinicians to identify patients who require cardiotoxicity prevention or treatment and to monitor the response to therapy in patients who have developed cardiotoxicity [ 232 , 238 ].…”
Section: Non-cardiovascular Etiologies Of Troponin Elevationmentioning
confidence: 99%